Targeted inhibition of PDGFRA with avapritinib, markedly enhances lenvatinib efficacy in hepatocellular carcinoma in vitro and in vivo: clinical implications - Bixing Zhao; Yang Zhou; Niangmei Cheng; Xiaoyuan Zheng; Geng Chen; Xin Qi; Xiangzhi Zhang; Fei Wang; Qiuyu Zhuang; Yehuda G. Assaraf; Xiaolong Liu; Yingchao Wang; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Lenvatinib, a tyrosine kinase receptor inhibitor, has emerged as a frontline therapeutic strategy for the management of advanced hepatocellular carcinoma (HCC). However, the modest response rate observed with lenvatinib and the rapid emergence of chemoresistance highlight the urgent need to elucidate the underlying molecular mechanisms. Herein we aimed at identifying the molecular mechanisms underlying lenvatinib resistance in HCC and investigated the efficacy of targeted combination therapies to surmount this chemoresistance. Methods We utilized CRISPR/Cas9 gene knockout screening combined with transcriptome sequencing of lenvatinib-resistant HCC cell lines to identify resistance-associated genes. PDGFRA overexpression was validated in human lenvatinib-resistant HCC cells. We further corroborated the in vitro and in vivo role of PDGFRA in lenvatinib resistance using a PDGFRA inhibitor, avapritinib, employing a mouse orthotopic HCC model, patient-derived organoids (PDO), and patient-derived xenografts (PDX). The association between PDGFRA expression and patient prognosis was also assessed. Mechanistic studies were conducted to elucidate the signaling pathways contributing to lenvatinib resistance mediated by PDGFRA. Results PDGFRA overexpression was identified as a key determinant of lenvatinib-resistance in HCC cells. Consistently, ectopic PGDGFRA overexpression conferred lenvatinib resistance upon HCC cells. Treatment with the PDGFRA inhibitor avapritinib sensitized HCC cells to lenvatinib in mouse orthotopic HCC, PDO, and PDX models. Increased PDGFRA expression was correlated with poor prognosis in HCC patients. Mechanistic studies revealed that lenvatinib treatment or PDGFRA overexpression promoted HCC resistance through the PTEN/AKT/GSK-3β/β-catenin signaling pathway. Conclusions Our findings demonstrate that PDGFRA overexpression mediates lenvatinib resistance in HCC and that targeting PDGFRA with avapritinib, surmounts this resistance. Furthermore, the PTEN/AKT/GSK-3β/β-catenin pathway was implicated in lenvatinib resistance, providing a potential therapeutic strategy for HCC patients displaying lenvatinib resistance. Further clinical studies are warranted to validate these findings and to explore the clinical application of PDGFRA-targeted therapies in HCC treatment.